Effect of Terminal Water Stress on Phenological, Morpho-Physiological, and Yield and Its Attributing Traits of Bread Wheat Genotypes - Poudel, Anil; Ghimire, Surya Kant; Achraya, Barun Dev; Ojha, Bishnu Raj; Thapa, Dhruba Bahadur (Current Topics in Agricultural Sciences Vol. 4, 2021)
The field experiment with 50 bread genotypes was carried out at the research farm of Agriculture and Forestry University, Rampur, from December 2014 to April 2015 to determine the morpho-physiological traits, grain yield and its attributing traits in advanced lines and commercial varieties of bread wheat associated with drought tolerance. The field experiment was carried out in alpha lattice design with two replications under irrigated and drought environments. The outcomes of a combined analysis of variance and mean comparisons revealed that all genotypes differed significantly in both conditions and for growing conditions. Mean values of all the morpho-physiological yield and its attributing traits compared decreased performance of genotypes under drought stress conditions compared to irrigated conditions. In drought stress conditions, the genotype WK 2507 yielded the most (2.4 tons/ha), while the genotype WK 2513 yielded the least (0.095 tons/ha). In irrigated conditions, the genotype WK 2437 yielded the most (2.94 tons/ha), while the genotype WK 2523 yielded the least (0.272 tons/ha). However, genotypes WK 2525, WK 2507, Munal#1, and WK 2437 outperformed others in terms of grain yield in both drought and irrigated conditions. WK 2507, WK 2503, and WK 2524 were promising lines for drought conditions. Correlation studies under drought conditions showed the grain yield has a significant positive correlation with thousand- grain weight. It has a significant negative correlation with days to heading and flag leaf senescence under both drought and irrigated conditions.